Effect of oxidation-reduction cycles on steam-methane reforming kinetics over a nickel-based catalyst. (17th May 2019) - Navarro, M.V.; Plou, J.; López, J.M.; Grasa, G.; Murillo, R.
Abstract: The paper presents a detailed analysis of the effect of a high number of oxidation-reduction cycles on the steam-methane reforming process over a commercial Ni-based catalyst under conditions of intrinsic kinetics. These cycles take place within the sorption-enhanced steam-methane reforming process for hydrogen production including sorbent regeneration step. Experiments of steam-methane reforming and reverse water-gas shift reactions were carried out to obtain a complete characterisation of the system kinetics. After 80 cycles, methane conversion increased, while carbon dioxide conversion remained fairly constant. After 125 cycles, methane showed no significant changes in conversion compared to the increase exhibited by carbon dioxide. The kinetic model of Xu and Froment fitted the experimental results to provide the activation energies of the main reactions, which presented an evolution with redox cycles in line with the trends observed for conversion. The reactions with methane initially reduced their activation energy, facilitating conversion, while the reactions with carbon dioxide initially kept the activation energy constant, subsequently reducing it. Highlights: Effect of redox cycles on steam-methane reforming kinetics. Successful application of the Xu and Froment kinetic model. Activation energy evolution up to 125 redox cycles. Methane and carbon dioxide reactants showed different evolution patterns.